Effects of fecal microbiota transplantation on metabolic health of DBA mice - Ye, Wenxin; Fan, Jinghui; Wu, Wenzi; Chen, Zhuo; Huang, Qixin; Qian, Lichun (Frontiers in Microbiology, 2024)
Numerous studies have demonstrated that C57BL/6 mice exhibit superior growth rates and overall growth performance compared to DBA mice. To investigate whether this discrepancy in growth performance is linked to the composition of gut microorganisms, we conducted fecal microbiome transplantation (FMT) experiments. Specifically, we transplanted fecal fluids from adult C57BL/6 mice, high-fat C57BL/6 mice, and Wistar rats into weaned DBA mice (0.2mL/d), and subsequently analyzed their gut contents and gene expression through 16S rRNA sequencing and transcriptome sequencing. During the test period, C57BL/6 mice and Wistar rats were provided with a normal diet, and high-fat C57BL/6 mice were provided with a high-fat diet.The results of our study revealed that mice receiving FMT from all three donor groups exhibited significantly higher daily weight gain and serum triglyceride (TG) levels compared to mice of CK group. 16S rRNA sequensing unveiled substantial differences in the abundance and function of the gut microbiota between the FMT groups and the CK group. Transcriptome analysis revealed a total of 988 differential genes, consisting of 759 up-regulated genes and 187 down-regulated genes, between the three experimental groups and the CK group. Functional Gene Ontology (GO) annotation suggested that these genes were primarily linked to lipid metabolism, coagulation, and immunity. Pearson correlation analysis was performed on the differential genes and clusters, and it revealed significant correlations, mainly related to processes such as fatty acid metabolism, fat digestion and absorption, and cholesterol metabolism.In summary, FMT from dominant strains improved the growth performance of DBA mice, including body weight gain, institutional growth, and immune performance. This change may be due to the increase of probiotic content in the intestinal tract by FMT and subsequent alteration of intestinal gene expression. However, the effects of cross-species fecal transplantation on the intestinal flora and gene expression of recipient mice were not significant.